2003
DOI: 10.1191/0269215503cr567oa
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of a nursing home placement from a non-acute geriatric hospital

Abstract: These factors should be the target of specific rehabilitation in an attempt to reduce the risk of discharge to a nursing home and improve patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…éven though their involvement in the decision-making process is a fundamental right set down in French Law as in other western countries, fewer than 40% of long-term care residents in the "éhPa 2000" survey considered that they were adequately involved in the process leading to their placement (28). the independent role played by cognitive impairment in institution admission in our study has also been underlined in other reports (29)(30)(31). More recently, gaugler et al (23) found cognitive impairment to be among the strongest predictors of institutionalisation.…”
Section: Figuresupporting
confidence: 63%
“…éven though their involvement in the decision-making process is a fundamental right set down in French Law as in other western countries, fewer than 40% of long-term care residents in the "éhPa 2000" survey considered that they were adequately involved in the process leading to their placement (28). the independent role played by cognitive impairment in institution admission in our study has also been underlined in other reports (29)(30)(31). More recently, gaugler et al (23) found cognitive impairment to be among the strongest predictors of institutionalisation.…”
Section: Figuresupporting
confidence: 63%
“…16,17 All of these factors may contribute to prolonged hospitalisation and/or increase the likelihood of discharge to residential care. 18,19 Falls among patients in the hospital setting also have a significant impact on the health care provider. Such adverse events may be considered as a surrogate indicator of the quality of care provided.…”
Section: What Are the Implications For Practitioners?mentioning
confidence: 99%
“…2 Falls can result in increased length of hospital stay, discharge to a long-term care facility, and increased costs. 3,4 In a retrospective, casecontrol study of hospital falls, patients with serious fall-related injury had charges that were $4,233 higher than those for patients who did not fall. 3 In addition to the physical harm that may result, falls may also contribute to emotional injury and decreased quality of life.…”
mentioning
confidence: 99%